2022
DOI: 10.1111/fwb.14003
|View full text |Cite
|
Sign up to set email alerts
|

Body stores of emergent aquatic insects are associated with body size, sex, swarming behaviour and dispersal strategies

Abstract: Dispersal is a determining step in the life cycle of insects and a key factor of their energy budget. If the body stores of terrestrial insects are relatively well‐documented, those of merolimnic insects (i.e., with aquatic larvae and terrestrial winged adults) remain poorly investigated. We assayed the body stores (protein, carbohydrate and lipid contents) of 18 families of merolimnic insects, encompassing a wide diversity of biological and ecological traits. We highlighted allometry between body stores and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
0
2
1
Order By: Relevance
“…The results are in agreement with those reported earlier in the oriental armyworm, Mythimna separata (Walker) (Lepidoptera: Noctuidae), under both fluctuating and constant temperatures (Lv & Xie, 2022), in the coccinellid beetle, C. septempunctata , over a range of geographic locations (Zhou et al, 1995), and in the Mediterranean fruit fly, Ceratitis capitata Wiedemann (Diptera: Tephritidae), over a range of diets (Nestel et al, 2005). Contrary to our findings, Gerber et al (2022) reported more triglycerides in males than their conspecific females in swarming taxa of merolimnic insects.…”
Section: Discussioncontrasting
confidence: 99%
“…The results are in agreement with those reported earlier in the oriental armyworm, Mythimna separata (Walker) (Lepidoptera: Noctuidae), under both fluctuating and constant temperatures (Lv & Xie, 2022), in the coccinellid beetle, C. septempunctata , over a range of geographic locations (Zhou et al, 1995), and in the Mediterranean fruit fly, Ceratitis capitata Wiedemann (Diptera: Tephritidae), over a range of diets (Nestel et al, 2005). Contrary to our findings, Gerber et al (2022) reported more triglycerides in males than their conspecific females in swarming taxa of merolimnic insects.…”
Section: Discussioncontrasting
confidence: 99%
“…There can be at least two potential alternative explanation of the observed pattern of female biased dispersal in our assays. First, females in D. melanogaster are, on an average, larger than males (Horabin, 2005), and are hence expected to have higher amount of stored resources in their body (Gerber et al, 2022). Body size dependent dispersal rate is not unheard of (Bonte et al, 2012, see Anderson and Fahimipour, 2021 for a relatively recent exposition relevant to stability of metacommunity).…”
Section: Discussionmentioning
confidence: 99%
“…A shift in consumed prey can also involve a change in the available nutrients for the predator (Toft, 2013). In fact, the nutrient content varies depending on the insect order, the mating system and the dispersal strategy (Gerber et al, 2022), which may affect spider performance including the web quality (Blamires et al, 2009) or the reproductive success (Salomon et al, 2008), parameters especially related to the availability of proteins and lipids, respectively. Such an impact on the individual level may, in the long run, have consequences for the development of spider populations: densities of web-building riparian spiders usually decrease with altered or reduced aquatic subsidy (Kato et al, 2003;Marczak and Richardson, 2007;Paetzold et al, 2011) which could lead to propagating effects on consumers feeding on spiders (Recalde et al, 2020).…”
Section: Spider Dietmentioning
confidence: 99%